Adverse reproductive outcomes from exposure to environmental mutagens - Srám, R J; Binková, B; Rössner, P; Rubes, J; Topinka, J; Dejmek, J (Mutation research, 1999)
The effect of environmental pollution on reproductive outcomes has been studied in the research project 'Teplice Program' analyzing the impact of air pollution on human health. Genotoxicity of urban air particles <10 microm (PM10) in in vitro system was determined by the analysis of DNA adducts. The highest DNA binding activity was observed in aromatic fraction, identifying DNA adducts of carcinogenic polycyclic aromatic hydrocarbons (PAHs) presumably diolepoxide-derived from: 9-hydroxybenzo[a]pyrene (9-OH-B[a]P), benzo[a]pyrene-r-7,-dihydrodiol-t-9,10-epoxide[+] (anti-BPDE), benzo[b]fluoranthene (B[b]F), chrysene (CHRY), benz[a]antracene (B[a]A), indeno[1,2,3-cd]pyrene (I[cd]P). Reproductive studies were conducted in both females and males. A study of the effects of PM10 exposure on pregnancy outcomes found the relationship between the intrauterine growth retardation (IUGR) and PM10 levels over 40 microg/m(3) in the first gestational month (Odds Ratio for 40-50 microg/m(3)50 microg/m(3)=1.9). Selected biomarkers were analyzed in venous blood, cord blood (chromosomal aberrations, comet assay) and placenta (DNA adducts, genetic polymorphisms of GSTM1 and NAT2 genotypes) of women enrolled in a nested case-control study. DNA adduct levels were higher in polluted vs. control districts, in smoking vs. nonsmoking mothers, and in GSTM1 null genotype, which was more pronounced in polluted district. No effect of air pollution was observed by cytogenetic analysis of chromosomal aberrations or by comet assay. The reproductive development of young men was followed by measures of semen quality, adjusted for ambient SO(2) exposure. The analysis identified significant associations with air pollution for <13% morphologically normal sperm, <29% sperm with normal head shape, <24% motile sperm. Analysis of aneuploidy in human sperm by FISH showed, aneuploidy YY8 was associated with season of heaviest air pollution. These findings are suggestive for an influence of air pollution on YY8 disomy. All these results indicate that air pollution may increase DNA damage in human population, which may be even higher for susceptible groups. Biomarkers of exposure (DNA adducts) and susceptibility (GSTM1 and NAT2) may indicate the risk of presumable low environmental exposure. Pregnancy outcome and semen studies imply that relatively low air pollution (higher than 40 microg PM10/m(3)) can significantly increase the adverse reproductive outcomes affecting both genders.
Keywords: mutageny; Mutagenicity Tests; In Vitro Techniques; látky znečišťující vzduch; Reproduction; Semen; vystavení vlivu životního prostředí; Air Pollutants; Male; těhotenství; Česká republika; testy genotoxicity; DNA Adducts; výsledek těhotenství; mužské pohlaví; studie případů a kontrol; Environmental Exposure; techniky in vitro; Mutagens; Czech Republic; Infant, Newborn; ženské pohlaví; novorozenec; Humans; sperma; Pregnancy; biologické markery; Pregnancy Outcome; Chromosome Aberrations; chromozomální aberace; rozmnožování; Biomarkers; Female; adukty DNA; lidé; Case-Control Studies